2019
DOI: 10.1103/physrevb.100.205119
|View full text |Cite
|
Sign up to set email alerts
|

Impurity-induced resonant states in topological nodal-line semimetals

Abstract: Nodal-line semimetals are characterized by a kind of topologically nontrivial bulk-band crossing, giving rise to almost flat surface states. Yet, a direct evidence of the surface states is still lacking. Here we study theoretically impurity effects in topological nodal-line semimetals based on the Tmatrix method. It is found that for a bulk impurity, some in-gap states may be induced near the impurity site, while the visible resonant impurity state can only exist for certain strength of the impurity potentials… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Although we cannot determine the different defect types yet, further exploration of the impurity spectrum may provide extra information for a later determination [54]. The most frequently found defects are the diamond-shaped Zr-site defect and the X-shaped S-site defect, which are expected to be located within the top ZrS bilayer.…”
Section: Resultsmentioning
confidence: 95%
“…Although we cannot determine the different defect types yet, further exploration of the impurity spectrum may provide extra information for a later determination [54]. The most frequently found defects are the diamond-shaped Zr-site defect and the X-shaped S-site defect, which are expected to be located within the top ZrS bilayer.…”
Section: Resultsmentioning
confidence: 95%
“…The effects of a single impurity on the system with Dirac spectrum have been extensively studied [64][65][66][67][68][69][70][71][72]. Previously the impurity effects have been widely used for understanding the nature of the quasiparticle spectra in various unconventional superconductors [73][74][75][76][77] and topological systems [78][79][80][81][82]. It is shown that the local density of states (LDOS) around a Dirac point of the electronic spectrum is significantly disrupted by a sufficiently large impurity perturbation [64].…”
mentioning
confidence: 99%